Mediating Role of Organizational Commitment on HRM Pratices and Turnover Intention Relationship: An Empirical Evidence of Private Universities in Bangladesh. (Global Business Management Review (GBMR), 2012)
The present study was designed to examine the relationship between various HRM practices and faculty turnover intention among the private universities in Bangladesh. A total of 317 faculty members participated in the survey. Multiple regression analyses were used to test the hypotheses of the study. The results indicated that compensation, working conditions, job autonomy and job security were found strongly and negatively related to faculty turnover intention. The study also found organizational commitment (OC) as a partial mediator of the proposed relationship, while OC was full mediator for the relationship of job security and turnover intention. Limitations, implications and suggestions for future research are formulated.